Microbial community response to simulated diluted bitumen spills in coastal seawater and implications for oil spill response. Issue 5 (5th April 2022) - Cobanli, Susan E; Wohlgeschaffen, Gary; Ryther, Camilla; MacDonald, Jessica; Gladwell, Alison; Watts, Taylor; Greer, Charles W; Elias, Miria; Wasserscheid, Jessica; Robinson, Brian; King, Thomas L; Ortmann, Alice C
Abstract: Oil spills in coastal waters can have devastating impacts on local ecosystems, from the microscopic base through to mammals and seabirds. Increasing transport of diluted bitumen has led to concerns about how this novel product might impact coastal ecosystems. A mesocosm study determined that the type of diluent and the season can affect the concentrations of hydrocarbons entering the water column from a surface spill. Those same mesocosms were sampled to determine whether diluent type and season also affected the microbial response to a surface spill. Overall, there were no differences in impacts among the three types of diluted bitumen, but there were consistent responses to all products within each season. Although microbial abundances with diluted bitumen rarely differed from unoiled controls, community structure in these organisms shifted in response to hydrocarbons, with hydrocarbon-degrading bacteria becoming more abundant. The relative abundance of heterotrophic eukaryotes also increased with diluted bitumen, with few photosynthetic organisms responding positively to oil. Overall shifts in the microbial communities were minimal relative to spills of conventional oil products, with low concentrations of hydrocarbons in the water column. Oil spill response should focus on addressing the surface slick to prevent sinking or stranding to minimize ecosystem impacts. Abstract : Surface spills of different types of diluted bitumen in low-energy environments cause shifts in microbial community structure, but not changes in abundances with differences depending on the season.